CHARACTER EDUCATION VALUE IN SUPER 30 MOVIES - Dahlan, Zaini; Tambunan, DahlQurrota A?yuna (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2020)
Objectives in this study to describe the concept of character education in the movie Super 30. The research, which is a library research using the primary data source of the film Super 30 Vikas Bahl in 2019. Thus the method of data collection is documentation research Methode, while the analysis of data using content analyze from the contents of the film, then poured in a qualitative descriptive consisting of three activities, namely data collection as well as data reduction, data presentation, and the conclusion retrieval as well as data verification. The results of this study pointed out that (1) the concept of character education developed in the film Super 3 applies the value of modesty, responsibility, discipline, compassion, friendship, independence, hard work, and cooperation; and (2) methods used include methods of advice, habituation, and Solicit.